China-South Africa relations in the context of BRICS - Xiong, Hao-Fei (My University, 2012)
Emerging powers are becoming increasingly ubiquitous in the international arena. There are many factors which contribute towards the shift from western hegemony to a more balanced distribution of power: the global financial crisis weakening the economies of developed states, the rise of China and other emerging market states, and the increasing international grouping of the global south via official and non-official alliance networks. Focus on the newly formed BRICS group of Brazil, Russia, India, China and South Africa draws attention to one subset of this trend. South-south cooperation in the shape of a group of rising states attempting to combine international state action with synthesized common agendas breeds new implications in the balance of power currently present in the world system. Despite the novelty of the BRICS group, it represents a new growth pole in a multi polar world order which is steadily seeking to modify itself in the fulfilment of its member’s interests. It is undeniable that not only are its members advancing in political and economic clout, but garnering a common perspective as well, particularly in regards to collective actions within formal international institutions. The emergence of BRICS speaks to a greater complexity that is occurring in the international system, a heterogeneity that is spurred on by the rise of China and the increase of strategic alliances between prominent states within the global south. Moreover the broader China-Africa engagement is one such network which dramatically influences and changes traditional aspects of north-south relations and south-south relations. There is no doubt that the honed and fluid development of relations between China and South Africa has assisted South Africa’s ascension into the BRIC group. The maturing of China-South Africa relations within the framework of BRICS and broader China-Africa engagement is a unique dimension to a changing global order. Cooperation between China and South Africa, in correlation with BRICS agenda at a multilateral level in international institutions and on international topical issues in many ways epitomizes the complex and dynamic evolution of south-south cooperation.
M.A. University of the Witwatersrand, Faculty of Humanities (Dept. of International Relations), 2012